Hubungan Social Support dengan Quarter Life Crisis pada Mahasiswa Akhir Universitas Negeri Padang - Maia Welia Dinda; Yolivia Irna Aviani (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Quarter life crisis is a phenomenon that can occur in individuals in their 20s who experience a major transition in life, from the world of education to the world of work. This crisis arises due to extraordinary uncertainty about the future, confusion about the direction of life, and feelings of helplessness because there are too many choices available. Good social support from the environment such as emotiona/ appreciation support, material, information and companionship will help final year students experience the quarter life crisis phase. The purpose of this study was to determine the relationship between social support and quarter life crisis in final year students at Padang State University. This type of research is quantitative research with a research sample of 292 final year students using probability sampling techniques, namely cluster sampling techniques in determining the sample. The instruments used were the quarter life crisis questionnaire and the social support questionnaire. The results of the statistical analysis test of the study showed that if the significance value was 0.000 (p <0.05) it meant that the research hypothesis was accepted. There is a significant relationship between social support and quarter life crisis in final year students at Padang State University with a correlation value of -.615, this relationship is in the strong correlation category.